Teaching The Black Death With Systems Thinking - Swendson, David (Teaching History: A Journal of Methods, 2007)
Winston Churchill suggested that "history unfolds itself by strange and unpredictable paths,"1 but however that might be, too many students of history tend to view the unfolding as a disconnected series of events, or perhaps worse as a mere collection of facts. Over the past several years I have introduced a different method of teaching history concepts in a variety of course settings, as well as in presentations to groups. This method involves systems thinking or understanding how events are related to and influence each other and combine in series and feedback loops to create very complex patterns. I propose that it is the identification and understanding of these patterns that make history useful in understanding the past, dealing with the present, and planning for the future. In this paper I describe how system mapping can be used to clarify the events of the Black Death in Europe and I provide some sample "maps." (The four figures in the essay are examples from students maps.)